2021
DOI: 10.1371/journal.pntd.0009622
|View full text |Cite
|
Sign up to set email alerts
|

Miltefosine enhances infectivity of a miltefosine-resistant Leishmania infantum strain by attenuating its innate immune recognition

Abstract: Background Miltefosine (MIL) is currently the only oral drug available to treat visceral leishmaniasis but its use as first-line monotherapy has been compromised by an increasing treatment failure. Despite the scarce number of resistant clinical isolates, MIL-resistance by mutations in a single aminophospholipid transporter gene can easily be selected in a laboratory environment. These mutations result in a reduced survival in the mammalian host, which can partially be restored by exposure to MIL, suggesting a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…15 Our previous reports used BLI to demonstrate a striking MIL dependency of a resistant L. infantum strain, linked to lowered NK and NKT cell responses in the liver, leading to reduced IFN-γ production. 7,13 The differences in cidal dynamics between the reference drugs observed in this study corroborate previous findings in vitro, where the effect of PMM was slower than that of MIL 2 . PMM monotherapy was also found to be prone to fast relapse, originating from the bone marrow.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…15 Our previous reports used BLI to demonstrate a striking MIL dependency of a resistant L. infantum strain, linked to lowered NK and NKT cell responses in the liver, leading to reduced IFN-γ production. 7,13 The differences in cidal dynamics between the reference drugs observed in this study corroborate previous findings in vitro, where the effect of PMM was slower than that of MIL 2 . PMM monotherapy was also found to be prone to fast relapse, originating from the bone marrow.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…Although various bioluminescent Leishmania species and strains have already been used to monitor in vitro drug efficacy, , in vivo parasite fitness linked to drug resistance, , and the impact of (vaccine-induced) immune responses or interventions, , the application of BLI for in vivo drug potency has been scarce. Nevertheless, the kinetics of drug treatment have already been assessed in the hamster and the BALB/c mouse model. ,,, Álvarez-Velilla et al showed that BALB/c mice were seemingly cleared of infection after 5 days of MIL treatment at 40 mg/kg/day .…”
Section: Resultsmentioning
confidence: 99%
“…The L. donovani strain MHOM/ET/67/L82 was isolated from an Ethiopian VL-patient. Both were modified to express bioluminescent (PpyRE9) and/or fluorescent (DsRed) reporter proteins (LEM3323 WT PpyRE9 , LEM3323 WT PpyRE9/DsRed and L82 WT PpyRE9/DsRed ) 81 . Promastigotes were sub-cultured twice weekly at 25 °C in hemoflagellate-modified minimal essential medium (HOMEM, Gibco®), supplemented with 10 % inactivated fetal calf serum (iFCS), 200 mM L-glutamine, 16.5 mM NaHCO 3 , 40 mg/L adenine, 3 mg/L folic acid, 2 mg/L D-biotin, and 2.5 mg/L hemin.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were measured by flow cytometry using a MACSQuant® Analyzer 10 (Miltenyi Biotec) and analyses were performed using FlowLogic TM Software (Miltenyi Biotec) following specific gating strategies (Supplementary Table S2 , Supplementary Figs. S9 – 11 ) based on published methods 66 69 .…”
Section: Methodsmentioning
confidence: 99%